The Role of Mycelium-Based Biomaterials in Eco-Friendly Packaging and Product Design - Soelistianto, Farida Arinie; Haslinah, Andi; Megavitry, Rissa (West Science Nature and Technology, 2025)
This study explores the role of mycelium-based biomaterials in promoting environmentally friendly packaging and product design in Indonesia. Using a qualitative methodology, data were gathered through interviews with three key informants: a material scientist, a packaging industry expert, and a sustainable design entrepreneur. Thematic analysis conducted with NVIVO software revealed four major findings: (1) the environmental benefits of mycelium, including biodegradability and low energy production requirements; (2) challenges such as scalability, high costs, and limited awareness; (3) diverse applications in packaging and product design, including luxury markets; and (4) the critical role of government policy and stakeholder collaboration in driving adoption. These findings highlight the potential of mycelium-based biomaterials to contribute to Indonesia's sustainability goals by reducing plastic waste and fostering innovative eco-friendly solutions. However, addressing scalability and cost issues requires policy interventions and cross-sector collaboration.